Comparison of heat-labile enterotoxins from porcine and human strains of Escherichia coli. - Geary, S J (1982)
Heat-labile enterotoxins (LTs) from porcine EWD299) and human (H74-114) enterotoxigenic strains of Escherichia coli were isolated by a single-step galactose elution procedure. Although both strains had similar amounts of LT in their whole-cell lysates, H74-114 yielded a smaller quantity of purified LT than did EWD299. Immunodiffusion studies with specific antisera revealed that although the two LTs shared major antigenic determinants each also had unique antigens. Both also had shared and unique specificities in comparison with the cholera enterotoxin (choleragen). Differences also exist in the apparent molecular weights of their B-subunit oligomers (coligenoid) as well as in the B-subunit monomers. The monomer molecular weights are 11,500 for EWD299 porcine LT and 12,700 for H74-114 human LT. The results suggest that either this isolated human LT has a tetrameric coligenoid or it moves differently in sodium dodecyl sulfate gels for other reasons. The A-subunits of both LTs were similar in size (28,000 daltons), and both LTs were activated by mild proteolytic processing. Amino acid analysis showed a threefold increase in the level of tryptophan and two- and fourfold decreases in the levels of glutamic acid and methionine, respectively, in H74-114 LT compared with EWD299 LT. These structural and antigenic differences may prove to be significant in immunoprophylaxis of the cholera-coli family of enterotoxins. Further studies to define the extent of evolutionary drift of these toxins are needed.